Neuroprotection by the Cannabis-Related Products, Cannabidiol and Cannabigerol, and Their Associated Mechanisms of Action - Reyes-Parada, M (Elsevier, 2023)
The discovery and characterization of the endocannabinoid system (ECS) brought out years of research focusing on two aims. The study of its participation in the physiopathology in several diseases, including neurodegenerative disorders, and as a direct or indirect target for treating these disorders by cannabinoids or phytocannabinoids (i.e., specific compounds present in the Cannabis sativa plant). Preclinical evidence and some clinical data have shown the therapeutic potential of the most relevant phytocannabinoids, Δ9-tetrahydrocannabinol (Δ9-THC) and cannabidiol (CBD), but less for cannabigerol (CBG). In the present review, we summarized data focused on the therapeutic potential of CBD and CBG as neuroprotective agents. This property appears to be exerted by the direct or indirect activation of targets within the ECS and also by mechanisms nonmediated by the ECS. We provide information that could be useful for future CBD and CBG applications in human neurodegenerative diseases treatment. © 2023 Elsevier Inc. All rights reserved.